Any help for the helpers? Determinants of female infertility in oocyte donors - Omonigho, Ese W.; Anya, Okorie C.; Kalio, Ibilolia J.; Keke, Chidinma V.; Adisa, Kayode I.; Seriki, Aminat A.; Iheabunike, Gift I.; Hati, Stephen S. (International Journal of Research in Medical Sciences, 2024)
Background: Female infertility is a national problem for the family, and one of the major causes is ovarian dysfunction. Ovarian function can decline with increasing age and other factors, and this can affect oocyte quality. One of the ways to manage it is through oocyte donation; however, some oocyte donors also suffer from ovarian dysfunction. The aim of this study was to identify the determinants of infertility in young, unmarried females, with the aim of planning treatment strategies that may help reduce the burden of infertility. Methods: The study enrolled 335 individuals who presented for oocyte donation. The number of people who had their oocyte donation program cancelled due to fertility-related issues was analysed, and simple descriptive statistics were used for analysis. Results: Of the 330 participants, the age range was between 21 and 27 years, with a mean age of 23 years. About 19% of the participants had their oocyte donation program cancelled, and out of this proportion, 47% of them experienced poor ovarian response to stimulation with either a low anti-mullerian hormone level or a low antral follicular count on day 2 of their menstrual cycle. Conclusions: Identification and early management of this population of young females can invariably reduce the burden of infertility in the future.